Validation of Food-Frequency Questionnaires for Polyphenol Intake in Japanese Adults - FUKUSHIMA, Yoichi; KONDO, Kazuo; TAGUCHI, Chie; KISHIMOTO, Yoshimi (Journal of Nutritional Science and Vitaminology, 2021)
Estimations of individuals’ polyphenol intake contributes to the understanding of the health benefits of dietary polyphenol. We developed a food frequency questionnaire for polyphenol intake (FFQ) and a short-form FFQ for polyphenol intake (SF-FFQ) for assessing the polyphenol intake of Japanese. The aim of this study was to compare the relative validity of polyphenol intake derived from the FFQ with that from the SF-FFQ, using a 4-consecutive-d dietary record (DR) as the reference. Sixty Japanese subjects aged 30–69 y completed the 4-d DR and the two FFQs regarding their polyphenol intake in November 2019. The polyphenol intake values estimated by the DR, FFQ, and SF-FFQ were 1,057±524 mg/d, 1,061±537 mg/d and 1,015±491 mg/d, respectively. No significant differences were present in the estimated polyphenol intake between the 4-d DR and both FFQs. The correlation coefficient with the DR was 0.779 for the FFQ and 0.814 for the SF-FFQ. These results indicate that the total polyphenol intake in a Japanese population were accurately estimated by the FFQ and SF-FFQ.